An unusual case of delivery with central rupture of perineum and intact introitus - Mathe, Priyanka; Meena, Manisha; Bharti, Rekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Most women experience some degree of tear during childbirth and in some these can be extensive. Obstetrics injuries contribute 0.5-15% of vaginal deliveries. Here authors present a case of 23-year-old primigravida who presented at Safdarjung hospital New Delhi, Delhi, India with complaint of pain in perineum and excessive bleeding per vaginum. On examination, introitus was intact and there was central rupture of perineum which involved anal sphincter proximally and rectal mucosa distally. Patient was shifted to operation theatre for exploration and repair. She received 2 units of blood transfusion, antibiotics and laxatives. Patient was discharged on post-operative day 5 in satisfactory condition. Thus, authors emphasise the need of institutional delivery and prevention of perineal injuries which would further obviate the need for surgical repair and associated morbidity. In present era of easy communication and transport we still receive cases of unsupervised deliveries which gives us a strong motive to spread awareness for antenatal visits and care among this population.